Effects of forest fragmentation on biomass in tropical forests - Melito, Melina Oliveira (2016)
In spite tropical forests are the most important terrestrial global carbon sinks due to carbon storage in aboveground biomass, it is also the primary target of deforestation. The conversion of Tropical forests into anthropogenic areas might disrupt biological flux and also lead to severe microclimatic changes at forest edges. These combined effects can trigger profound changes in plant composition through both high mortality of fragmentation-sensitive species and proliferation of disturbed-adapted species which will ultimately impacts carbon storage. Thus, our main objective in this study was understand the role of human-induced disturbances in modulate the dimension of biomass loss at tropical forests. We applied a systematic literature review searching for empirical evidences that edge effects can drive biomass loss in tropical forests (Chapter 2). Our findings highlighted the gap of knowledge about the pattern and process related to biomass loss in tropical forests. To strengthen this understanding, we formulated a conceptual model linking landscape structure and patch-level attributes to severity of edge effects affecting aboveground biomass. Our model hypothesizes that habitat amount, isolation, time since edge creation, and the synergism between edge distance, patch size, and matrix type are the main drivers of biomass loss in anthropogenic tropical forests. We thus used a large plant dataset (18 503 trees ≥ 10 cm dbh) from 146 sites distributed across four Mexican and four Brazilian rainforest regions to test our conceptual model predictions, specifically the influence of forest cover, site isolation, edge distance, patch size and type of matrix on biomass (Chapter 3). We observed that carbon-rich sites presented species that are typical of old-growth forests (shade-tolerant, large-seeded, zoocoric) contrasting to carbon-poor sites composed by disturbed-adapted species (pioneer occupying the understory). Large shade-tolerant trees (≥ 40 cm dbh) were impacted severely by the combination of forest loss and edge effects. Edge distance, patch size, and the amount of open-matrix strongly influence small shade-tolerant trees (≤ 20 cm dbh). Although our results do not fully corroborate the initial predictions of the conceptual model, they support the idea that landscape composition interact with patch structure and ultimately impacts biomass stocks in fragmented tropical forests. Finally, we further investigated if the disturbance level of the region influences plant-structure responses to forest loss (Chapter 4). Biomass, but not plant density, was affected by forest loss in regions with intermediate disturbance levels, i.e. regions showing a combination of moderate deforestation (20-40% of remaining forest cover) disturbed during the past 30-60 years, high defaunation but harboring relictual populations of large-mammals, and areas mostly composed by heterogeneous matrices. In general, our findings highlight that both landscape composition and patch structure are the main drivers of biomass loss in Neotropical forests, and that the landscape context must be considered to obtain more reliable estimations of carbon emissions due to forest degradation. Landscape planning (e.g. restoration of forest cover) should be included in conservation strategies in order to sustain carbon storage. Moreover, we advocate that conservation initiatives will be less costly and more effective if implemented in areas under intermediate disturbance levels